3PC-065 Orodispersible films – an interesting dosage form!. (March 2019) - Sauer, S; Kohl, L; Veitinger, L; Zink, V; Hoppe-Tichy, T
Abstract : Background: Orodispersible films (ODF)are described in the European Pharmacopoeia. However only a few ODF products are on the market, of which most are not medicines. ODFs provide an alternative formulation for those with swallowing difficulties, for example, paediatric and geriatric patients. An advantage of this formulation is that when they come into contact with water they become sticky, making it difficult to spit out. Purpose: The aim was to develop a basis formulation of ODF. The formulation at the beginning of the manufacturing process should be fluid enough for pouring, but then solidify quickly. The resulting ODFs also should dissolve fast on contact with water and maintain good mechanical strength in handling. Material and methods: Three different solutions were created, consisting of water, glycerol and hypromellose (HM), differing in the hypromellose content of: solution I with 3% HM, solution II with 4% HM and solution III with 5% HM. Prepared solutions were degassed by ultrasound and films were formed with the help of a film-layering machine. All were dried at room temperature. The dried films were then cut into pieces of 4 cm 2 with a scalpel and the backing film removed. The taste was tested and the dissolution observed. Consequently, a piece of the film was placed in a dish with 20 ml of distilled water, every 10 s the dish was slightly agitated and the time to dissolution recorded. Results: Solutions were found to be easy to process: solution III was almost too viscous. After drying, all films were found to be clear and even. Solution I was found to be quite sticky on the surface. All were easy to peel off from the backing film. All were found to be tear-resistant enough to handle. All films tasted sweet, were sticky in the mouth and subsequently unable to be spat out. All dissolved within about 4 min. Solution II was found to be the optimal formulation. Conclusion: ODFs are very interesting and could extend the spectrum of dosage forms. In the future, further variants in composition will be investigated and drugs will be incorporated. References and/or acknowledgements: Thanks to the team of the IPMB for supporting the film production. No conflict of interest.